The bouncing barrier revisited: impact on key planet formation processes and observational signatures - Dominik, Carsten; Dullemond, Cornelis (Astronomy and astrophysics, 2024)
Context. A leading paradigm in planet formation is currently the streaming instability and pebble accretion scenario. Notably, dust must grow into sizes in a specific regime of Stokes numbers in order to make the processes in the scenario viable and sufficiently effective. The dust growth models currently in use do not implement some of the growth barriers suggested to be relevant in the literature. Aims. We investigate if the bouncing barrier, when effective, has an impact on the timescales and efficiencies of processes such as the streaming instability and pebble accretion as well as on the observational appearance of planet-forming disks.Methods. We implemented a formalism for the bouncing barrier into the publicly available dust growth model DustPy and ran a series of models to understand the impact. Results. We found that the bouncing barrier has a significant effect on the dust evolution in planet-forming disks. In many cases, it reduces the size of the typical or largest particles available in the disk; it produces a very narrow, almost monodisperse, size distribution; and it removes most μm-sized grains in the process, with an impact on scattered light images. It modifies the settling and therefore the effectiveness of and timescales for the streaming instability and for pebble accretion. An active bouncing barrier may well have observational consequences: It may reduce the strength of the signatures of small particles (e.g., the 10 μm silicate feature), and it may create additional shadowed regions visible in scattered light images. Conclusions. Modeling of planet formation that leans heavily on the streaming instability and on pebble accretion should take the bouncing barrier into account. The complete removal of small grains in our model is not consistent with observations. However, this could be resolved by incomplete vertical mixing or some level of erosion in collisions.
Gesehen am 08.07.2024